Evaluation and classification of productivity in reservoirs of Qigu Formation on the Fudong Slope,Junggar Basin - Yu, Jingwei; Wu, Aicheng; Wang, Xin; Liao, Mingjia; Qi, Liqi; Feng, Cheng; Gu, Shangxi; Cai, Yu (河南理工大学学报. 自然科学版, 2023)
The productivity of reservoirs in Qigu Formation was evaluated by 9 indexes,such as porosity,permeability,volume fraction of quartz,grain size,coefficient of anisotropy,abnormal pressure coefficient,compaction effect,volume fraction of calcite and chlorite,single sand body thickness were used to make evaluation and classification on productivity in reservoirs,all of which would improve productivity in reservoirs of Qigu Formation on the Fudong Slope of Junggar Basin. The result showed that the weight coefficient of each factors could be quantitatively calculated by two analysis methods,productivity of reservoirs in Qigu Formation was mainly controlled by compaction;Based on evaluation standard,reservoirs in Qigu Formation were divided into three types,and classification was anastomosed with current exploration and development situation,which showed feasibility of two methods was good.